S-layer protein gene of Acetogenium kivui: cloning and expression in Escherichia coli and determination of the nucleotide sequence. - Peters, J (1989)
Acetogenium kivui is anaerobically growing thermophilic bacterium with a gram-positive type of cell wall structure. The outer surface is covered with a hexagonally packed surface (S) layer. The gene coding for the S-layer polypeptide was cloned in Escherichia coli on two overlapping fragments by using the plasmid pUC18 as the vector. It was expressed under control of a cloned Acetogenium promoter or the lacZ gene. We determined the complete sequence of the structural gene. The mature polypeptide comprises 736 amino acids and is preceded by a typical procaryotic signal sequence of 26 amino acids. It i weakly acidic, weakly hydrophilic, and contains a relatively high proportion of hydroxyamino acids, including two clusters of serine and threonine residues. An N-terminal region of about 200 residues is homologous to the N-terminal part of the middle wall protein, one of the two S-layer proteins of Bacillus brevis, and there is also an internal homology within the N-terminal region of the A. kivui polypeptide.